The Action Research of Arabic Language Teachers in General Education: Awareness, Experience, and level of Application - Altonesi, Nabeelah Taher Ali (Journal of Educational and Psychological Sciences, 2021)
The study aimed to explore the awareness of Arabic language teachers in Madinah toward action research, their experience, and the level of practices in professional development. The qualitative approach was adopted, and data collection included focus group method of (22) Arabic language teachers in (6) schools at the three phases of Education: Primary, intermediate, and secondary in the academic year 1439/1440H. A Semi-structured interview was prepared. In addition, examined the portfolio of teachers’ performance, and other written evidence.The Credibility, Dependability and Confirmability criteria for the study were provided. The analysis of qualitative data shows results that deal with three aspects: First, Awareness: As most of the teachers did not have any knowledge of the concepts of action research. Weakness of spelling and composition was the most important problem in teaching Arabic language, as administrative and supervisory barriers had also a significant impact in the absence of the action research practices. Teachers have optimistic expectations of its future production and the proposal of specific procedures for its broadcasting, the most important of which is: training and exchange of experiences. Second, the teachers’ experience: participants showed deep conviction of the importance of action research and the desire for professional development. Third, Level of application: the variance of the teachers in the implementation of some specific steps to address the problems of language without commitment to scientific methodology or documentation.In light of the results, the study recommended enriching the professional development plan for Arabic language teachers with integrated training programs on action research. The study also recommended further research for a case study of successful models for implementation action research and to explore teachers’ experience in various disciplines and their practice.
Keywords: action research; Arabic language teachers; the nature of experience in action research; General education; level of application